Combined use of non‐laboratory methods for the practical diagnosis of endometritis in postpartum dairy cows. Issue 6 (24th August 2022) - Kusaka, Hiromi; Kimura, Taketoki; Nishimoto, Namiko; Sakaguchi, Minoru
Abstract: Background: : Postpartum endometritis can cause subfertility in cows and reduce the reproductive performance of dairy herds. Thus, there is a critical need to improve the accuracy of the diagnosis of this disease, particularly in dairy cows. Objectives: : This study confirmed the effects of the combined use of two non‐laboratory methods: Metricheck device (MT) and ultrasonography (UT) to detect signs of endometritis and therefore predict the likelihood of pregnancy. Methods: : The reproductive tract of 67 lactating Holstein cows (25 primiparous and 42 multiparous) was observed at 4 and 6 weeks postpartum using the MT and UT. The cows with flecks and more purulent material in the vaginal discharge were defined as MT‐positive, and the cows with uterine echogenic contents were defined as UT‐positive. The combined definition was also used; both the UT and MT results or either the UT or MT result had to be positive for the final decision to be positive. The true‐negative cows were determined as both MT‐UT‐negative. Results and discussion: When comparing the diagnostic results obtained by MT and UT, 37.3% and 32.8% of the total cows showed conflicting results at 4 and 6 weeks postpartum. The proportion of non‐pregnant cows until 200 days postpartum was significantly greater in both MT‐UT‐positive cows than in the true negative cows. The hazard ratios of pregnancy rate were 0.37 for both MT‐UT‐positives relative to the true negatives at 4 weeks postpartum. Similar significant differences were not detected using the MT or UT alone. These results indicate that a more severe effect on the chance of pregnancy could be detected in cows that are both MT‐UT‐positive compared with those positive for MT or UT alone. Conclusions: : The combined use of MT and UT could support veterinary practitioners in diagnosing endometritis, potentially improving the accuracy of predicting subsequent reproductive performance. Abstract : This study confirmed the effects of the combined use of two non‐laboratory methods: metricheck device (MT) and ultrasonography (UT) to detect signs of endometritis and therefore predict the likelihood of pregnancy. The probability of pregnancy until 200 days postpartum was reduced for both MT‐UT‐positives cows compared with the true negative cows. The combined use of MT and UT could support veterinary practitioners in diagnosing endometritis, potentially improving the accuracy of predicting subsequent reproductive performance.